Green Intellectual Capital as a Mediator of Good Corporate Governance and Firm Value: A Sharia Perspective - Ahmad Ryad; Yoyok Prasetyo (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the influence of the mechanism of good corporate governance (GCG) on the value of the company (FV), with Green Intellectual Capital (GIC) as a mediating variable in telecommunication companies listed on the Indonesia Stock Exchange (IDX) during the period 2016–2022. This research fills a gap in the literature related to the contribution of GIC in strengthening the relationship between GCG and FV, especially in sectors facing the pressures of digital transformation and environmental sustainability. The method used is Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of Smart PLS 3 software. Data was obtained through purposive sampling from 15 telecommunication companies. The results of the study show that GCG has a significant effect on GIC and company value, and that GIC mediates significantly the influence of GCG on company value. However, the direct influence of GCG on company value is more dominant than the indirect influence through GIC. These findings emphasize the importance of strengthening human resource capacity and knowledge-based sustainability strategies to improve the company's competitiveness in a sustainable manner.